Glucosinolate Profiles in Cabbage Genotypes Influence the Preferential Feeding of Diamondback Moth (Plutella xylostella) - Robin, Arif Hasan Khan; Hossain, Mohammad Rashed; Park, Jong-In; Kim, Hye R.; Nou, Ill-Sup (Frontiers in Plant Science, 2017)
Diamondback moth (DBM), Plutella xylostella L., is a devastating pest of cabbage worldwide whose feeding attributes are influenced by glucosinolate profiles of the plant. Identifying the specific glucosinolates associated with plants’ resistance mechanism can provide cues to novel points of intervention in developing resistant cultivars. We studied the DBM larval feeding preference and extent of damage on cabbage leaves via controlled glass-house and in vitro multiple- and two-choice feeding tests. These feeding attributes were associated with the individual glucosinolate profiles, analyzed by HPLC, of each of the eight cabbage genotypes using multivariate analytical approach to identify the glucosinolates that may have roles in resistance. Both the glass-house and in vitro multiple-choice feeding tests identified the genotype BN4303, BN4059 and BN40725 as the least preferred (resistant) and Rubra, YR Gold and BN3383 as most preferred (susceptible) genotypes by DBM larvae. The principal component analysis separated the genotypes based on lower feeding scores in association with higher contents of glucobrassicin, glucoiberin, glucoiberverin in one direction and 4-hydroxyglucobassicin, glucoerucin, glucoraphanin and progoitrin in opposite direction in a way to explain the major variation in resistant versus susceptible genotypes based on their extent of preference and leaf area damage. The simultaneous presence (or higher contents) of glucobrassicin, glucoiberin and glucoiberverin and the absence (or lower contents) of 4-hydroxyglucobassicin, glucoerucin, glucoraphanin, and progoitrin in the least preferred genotypes and vice-versa in most preferred genotypes indicated their apparent role as putative repellents and attractants of DBM larvae in cabbage genotypes, respectively. These novel findings add to the current knowledgebase on the roles of glucosinolates in plant-herbivore interactions and will be helpful in setting breeding priorities for improving the resistance against DBM in cabbage using conventional and biotechnological approaches.